2006
DOI: 10.2460/javma.229.9.1389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of certified health programs on the sale price of beef calves marketed through a livestock videotape auction service from 1995 through 2005

Abstract: Findings from this study indicated that implementation of the 2 most intensive certified health programs consistently increased the price of beef calves, and these price premiums increased over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 6 publications
3
17
0
Order By: Relevance
“…The plethora of bioinformatic techniques, together with other research areas, is generating terabytes of information, and the amount of biological data being generated is growing exponentially. Hence, the development of data mining technologies and software for proteomic data analyses requires the joint efforts of academic and clinical researchers with specialists in bioinformatics, mathematics, and statistics (6, 46, 67). …”
Section: Challenges For the Futurementioning
confidence: 99%
“…The plethora of bioinformatic techniques, together with other research areas, is generating terabytes of information, and the amount of biological data being generated is growing exponentially. Hence, the development of data mining technologies and software for proteomic data analyses requires the joint efforts of academic and clinical researchers with specialists in bioinformatics, mathematics, and statistics (6, 46, 67). …”
Section: Challenges For the Futurementioning
confidence: 99%
“…1 Additional factors that significantly influenced sale price were variation in body weight within calf lots (12 years), flesh score of calves within a lot (9 years), number of days between sale and delivery dates (11 years), and frame score of calves within a lot (7 years). 1 Additional factors that significantly influenced sale price were variation in body weight within calf lots (12 years), flesh score of calves within a lot (9 years), number of days between sale and delivery dates (11 years), and frame score of calves within a lot (7 years).…”
Section: Discussionmentioning
confidence: 99%
“…1 One noteworthy difference between video auctions and traditional auctions is that optimum lot size is larger at video auctions because of the inability of buyers to pool video auction lots for shipments and their desire to match lot size with that specified by feedlots. Analysis of the data for the study reported here revealed that producers have consistently enhanced the market price of their calves by selling crossbred steer calves with a medium or large frame in large lots with uniformity of quality, weight, and breed within the lots.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations